Meta-análise sobre o uso de suplemento energético para novilhas de corte em pastagens de estação fria - Martini, Amanda Carneiro (2019)
Meta-analysis is a procedure that combines results from several studies to make a reproducible and quantifiable synthesis of the data. The objective of this meta-analysis was to characterize the individual performance, by area and the stocking rate in winter pastures with or without supplements. The variables used for analysis were collected in seventeen experiments conducted at UFSM, RS-Brazil between 1999 and 2017. Four hundred and thirty-five Angus heifers and Charolais x Nellore crossbreeds, with an initial age of eight months and body weight (BW) of 160.9 ± 22.6 kg were used. The experimental animals received energetic supplement at a ratio of 0.8% dry matter (DM), provided daily at 14:00. The data were analyzed by the statistical program R, version 3.5.0, 'meta' package, 'metacont' function. The supply of supplement provided an increase in average daily gain, body condition score gain and final weight of 11.1%, 20,0% and 5.2%, respectively. The highest weight gain per area was obtained with higher levels of supply than 1.2% of BW and the stocking rate presented an increasing linear relation with the level of supplement supply. The use of supplement for heifers on temperate pasture provides greater individual gain per unit area and stocking rate